Mary Engelbreit's Mother Goose one hundred best-loved verses - Engelbreit, Mary 1952- (HarperCollinsPublishers, 2005)
An illustrated collection of nearly one hundred nursery rhymes, including "Twinkle, Twinkle, Little Star" and other familiar poems, as well as "Mary had a Pretty Bird" and other less familiar ones